2009
DOI: 10.1111/j.1365-2702.2008.02647.x
|View full text |Cite
|
Sign up to set email alerts
|

Improved quality and comprehensiveness in nursing documentation of pressure ulcers after implementing an electronic health record in hospital care

Abstract: Education related to the use of the electronic health record and evidence-based pressure ulcer prevention should be provided to the nurses. To facilitate documentation, the templates need to be refined to be more user-friendly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 20 publications
1
62
0
3
Order By: Relevance
“…This fact contrasts with an investigation on the completeness of PU records in the electronic medical record that indicated that 73% of nurses did not use standardized language and documented the nurses' interventions in free text (26) . According to the authors, standardized expressions were imprecise and moved away from the language commonly used by nurses.…”
Section: Completenessmentioning
confidence: 63%
See 1 more Smart Citation
“…This fact contrasts with an investigation on the completeness of PU records in the electronic medical record that indicated that 73% of nurses did not use standardized language and documented the nurses' interventions in free text (26) . According to the authors, standardized expressions were imprecise and moved away from the language commonly used by nurses.…”
Section: Completenessmentioning
confidence: 63%
“…In contrast, in the other events, follow-up care was recorded at a higher percentage compared with recording health problems of both SSIs (86.3%) and AP (79.7%). On the other hand, when nurses must provide specific descriptions, such as characteristics of the injured tissue or the exudate, they use free text more often (26) . This situation in our research is not only limited to PU events but also SSIs.…”
Section: Completenessmentioning
confidence: 99%
“…To the best of our knowledge, no other studies in nursing homes have shown the effects of using a CDSS on the completeness and comprehensiveness of nursing documentation, though several studies have shown improved documentation after educational interventions in paper-based [40,47] and electronic health records [39,48].…”
Section: Discussionmentioning
confidence: 99%
“…A structured format for recording has been effective at increasing the quality of nursing documentation [39,49]. A study conducted in a Swedish hospital showed that both the quality and comprehensiveness of PU documentation significantly improved after implementing an EHR system with pre-formulated templates [39]; however, the study had a before-after design with no control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation